FAKTOR-FAKTOR YANG MEMENGARUHI KETERANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN TAKALAR - M. Wahyuddin Abdullah (AkMen JURNAL ILMIAH, 2016)
The purpose of this study was to: 1) To determine the effect of human resources to the reliability of financial reporting of local government, 2) To determine the effect of the use of information technology to the reliability of financial reporting of local government, 3) To determine the influence of the internal control system of the reliability of financial reporting of local government , 4) To determine the effect of the application of the accrual basis to the reliability of financial reporting of local government. The author uses a quantitative approach to address these problems using primary data in the form of a questionnaire distributed to all respondents. Respondents in this study is the head SKPD, Head of Finance and Staff Division of Accounting / Finance Administration throughout SKPD contained in Takalar. The number of questionnaires issued in this study were 50 pieces of questionnaires sent to 35 SKPD in Takalar. But after going through the questionnaire collection phase, was only obtained 46 respondents who returned. Data used in this research is primary data obtained from the respondents on the questionnaire that was sent directly to each SKPD. Before analyzing the data, researchers to test the validity and reliability of the 30 respondents to indicate the extent to which the questionnaire can be trusted and relied upon. The data analysis technique used in this study is multiple regression analysis techniques. Results of testing the hypothesis in this study indicate that human resource capacity and utilization of information technology does not affect the reliability of financial reporting of local government. However, the internal control system and the implementation of accrual based in this study significantly affect the reliability of financial reporting local government.